Greetings from new Nashville : how a sleepy southern town became "it" city - Haruch, Steve, 1974- (Vanderbilt University Press, 2020)
"A collection of journalism and essays that traces the transformation of Nashville over the last two decades through journalistic essays about specific facets of that transformation"--